Advanced Computing and Systems for Security Volume Eight - Chaki, Rituparna; Cortesi, Agostino; Saeed, Khalid; Chaki, Nabendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book includes extended versions of selected papers discussed and presented at the 5th International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2018) held in Kolkata, India on February 9-11, 2018. The symposium was organized by the University of Calcutta's Department of Computer Science & Engineering and A. K. Choudhury School of Information Technology, and the International partners were Ca Foscari University of Venice, Italy and Bialystok University of Technology, Poland. Reflect the symposium's sessions, the book discusses topics such as biometrics, image processing, pattern recognition, algorithms, cloud computing, wireless sensor networks and security systems.
Chapter 1: Enhancing security in ROS -- Chapter 2: Byte Label Malware Classiﬁcation using Image Entropy -- Chapter 3: Big Data Security and Privacy: New Proposed Model of Big Data with Secured MR layer -- Chapter 4: The Concept of In-Vehicle System for Human Presence and Their Vital Signs Detection -- Chapter 5: Disaster Management System Using Vehicular Ad hoc Networks -- Chapter 6: An ensemble based approach towards sensitive miRNA target prediction -- Chapter 7: A Computer-aided Hybrid framework for early diagnosis of Breast Cancer -- Chapter 8: Naive Bayes and Decision Tree Classifier for Streaming Data using HBase.
Keywords: Computational intelligence; Signal processing; Data protection; Image processing -- Digital techniques; Computer vision; Big data; Computational Intelligence; Signal, Speech and Image Processing; Data and Information Security; Computer Imaging, Vision, Pattern Recognition and Graphics; Big Data